PERANCANGAN JOB SAFETY ANALYSIS DI PT CITRA TRANSPORT LOGISTIC PADA DEPARTEMEN MEKANIK DI UNIT DUMP TRUK - Mohammad Saifussuja Al Faqih; Endi Furqon; Ogie Kustiadi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
lack of supervision at work and lack of identification of potential hazards in the workplace. Make recommendations for improvement to reduce the impact of OSH risks. Using the job Safety analysis method, for each potential hazard, the severity and likelihood values ​​will be calculated using the Australian Standard/New Zealand Standard matrix. Research shows that there are 2 low potentials, 19 medium potentials and 3 high potentials. The results obtained are still a lot of hazard risks with medium risk potential, so it can be said that the work activities carried out by workers have not met the safe conditions. Recommendations can be made by making the Job Safety Analysis worksheet as a corrective action, the JSA worksheet as well as an evaluation reference to the deviations that occur. As a preventive measure the emergence of potential hazards can use the design of operational standards procedures for standardization